Gambaran Hasil Pemeriksaan Tekanan Darah antara Peserta Prolanis yang Memperoleh dengan Tidak Memperoleh Pelayanan Kontak Tidak Lansung - ICHWAN HANDOYO (BPJS Kesehatan, 2023)
The prevalence of chronic diseases constantly increases in Indonesia. Chronic diseases greatly affect the quality of human resources and have an impact on increasing healthcare costs. BPJS Kesehatan has constructed a healthcare system for Jaminan Kesehatan Nasional (JKN) members with a chronic disease, known as the Chronic Disease Management Program abbreviated as PROLANIS. Besides that, BPJS Kesehatan has developed indirect contact healthcare so that PROLANIS participants’ health status can be monitored to avoid complications while still complying with recommendations for physical distancing during the Covid-19 pandemic. Through this research, the writer aimed to describe quantitatively the frequency of PROLANIS Participants' checking their health at primary health care and the blood pressure test based on the frequency of indirect contact healthcare. The research is a descriptive study on secondary data of PROLANIS Participants’ health examination results from January 2021 to June 2022 by the primary health care in the BPJS Kesehatan Madiun branch working area. The results showed that the proportion of PROLANIS participants who regularly visited the primary health care for check-ups was greater in those who received indirect contact healthcare (29,35%) than those who did not (17,0 %). The percentage of PROLANIS participants receiving indirect contact healthcare with controlled blood pressure was 12,73%. While those who did not receive indirect contact healthcare with controlled blood pressure were 14,30%.